Runoff Water in Cocoa Plantation as Affected by Rorak Number and Mulch Type - Sri Wahyuni; Purwanto Purwanto; John Bako Baon (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Soil erosion is a serious problem in the field of ecology and environment. Providing rorak (small blocked ditches) and mulches as an alternative conservation action is expected to minimize water runoff. The purpose of this study was to examine the effects of combination of rorak and mulches in controlling water runoff in a cocoa farm. Location of this research was in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute during rainy season in early 2015. This research used a nested design in which there is a complete factorial design of random groups that every combination treatment was repeated three times. Each experiment plot consisted of 16 cocoa trees of eight years old. The first factor was rorak treatment consisted of without rorak, 9 rorak per 16 trees (plot) and 16 rorak per 16 trees, whereas the second factor was mulch treatment consisted of control (without mulch), cocoa leaves as mulch and rice straw mixed with cocoa leaves as mulch. Rorak collecting runoff water was made of aluminum with a length of 40 cm, width 30 cm and  high 30 cm. Observation of runoff water was carried out early every morning. The results showed that increased number of rorak combined with cocoa leaf and rice straw significantly controlled runoff water compared to control. Rorak and mulch treatments were able to reduce runoff water compared to control. High number of rorak per plot increased the effectiveness in controlling runoff water when it was combined with mulch especially mixture of wide leaf (cocoa leaf) and needleshaped leaf (rice straw). Treatment of 16 rorak in every 16 trees with cocoa leaves and rice straw mulch could reduce runoff water by 82.8% compared to a control.